2000
DOI: 10.1111/j.1749-6632.2000.tb05246.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tight Junction Permeability Can Result from Protein Kinase C Activation/Translocation and Act as a Tumor Promotional Event in Epithelial Cancers

Abstract: Exposure of LLC‐PK1 epithelial cell cultures to phorbol ester tumor promoters causes immediate translocation of protein kinase C‐α (PKC‐α) from cytosolic to membrane‐associated compartments. With a very similar time course, a dramatic and sustained increase in tight junctional (paracellular) permeability occurs. This increased permeability extends not only to salts and sugars but macromolecules as well. Fortyfold increases of transepithelial fluxes of biologically active EGF and insulin occur. Recovery of tigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 30 publications
1
44
1
Order By: Relevance
“…Our results suggest that PKCε's role in metastasis may be related to its ability to impair the barrier function (and cell adhesion) through phosphorylation of TJ proteins such as claudin-4. These findings are consistent with a number of studies that have previously shown that phosphorylation of various claudin proteins can decrease TJ integrity [32,35,[51][52][53][54], although phosphorylation of claudin-1 has also been shown to promote barrier function [29,31]. However, it is important to note that TJ disruption likely occurs through multiple mechanisms.…”
Section: Discussionsupporting
confidence: 90%
“…Our results suggest that PKCε's role in metastasis may be related to its ability to impair the barrier function (and cell adhesion) through phosphorylation of TJ proteins such as claudin-4. These findings are consistent with a number of studies that have previously shown that phosphorylation of various claudin proteins can decrease TJ integrity [32,35,[51][52][53][54], although phosphorylation of claudin-1 has also been shown to promote barrier function [29,31]. However, it is important to note that TJ disruption likely occurs through multiple mechanisms.…”
Section: Discussionsupporting
confidence: 90%
“…PKC isoforms in the gastrointestinal tract are involved in several vital intracellular pathways, including cell proliferation/cytostasis (Batlle et al, 1998;Verstovsek et al, 1998;Assert et al, 1999;Umar et al, 2000), cell differentiation (Abraham et al, 1998;Verstovsek et al, 1998;Frey et al, 2001), apoptosis (Chang and Tepperman, 2001;Frey et al, 2001), cell adhesion (Batlle et al, 1998;Hollande et al, 2003), membrane remodeling (Song et al, 1999(Song et al, , 2002, epithelial migration (Andre et al, 1999), transepithelial permeability (Marano et al, 2001), ion secretion (Van den Berghe et al, 1992;Yoo et al, 2001), receptor and brush border enzyme expression (Murray et al, 2002), cytoskeletal modulation (Fasano et al, 1995;Banan et al, 2002aBanan et al, ,c,d, 2003aBanan et al, ,b, 2004a, tight junction modification , and epithelial responses to inflammatory Tepperman, 2001, 2003), cytotoxic Chang and Tepperman, 2001), and carcinogenic (Pongracz et al, 1995;Murray et al, 1999Murray et al, , 2002Perletti et al, 1999;Mullin et al, 2000) mediators. These multiple roles suggest that this group of enzymes is involved in the regulation of the health and damage of epithelial cells and the intestinal barrier.…”
Section: Protein Kinasesmentioning
confidence: 99%
“…PKC-␣ has been associated with several cell functions. Mullin et al (2000) and showed that phorbol ester tumor promoters, which are general PKC activators, cause immediate translocation of PKC-␣ from cytosolic-to membrane-associated compartments. This translocation is associated with paracellular leakiness and multilayered cell growth.…”
Section: Conventional Pkcsmentioning
confidence: 99%
“…5,6 Thus, oral administration would be an efficient strategy for treatment of colorectal cancer, since the chemotherapeutic agent could effectively reach the tumor site. However, oral administration of PTX is associated with a number of limitations.…”
Section: Discussionmentioning
confidence: 99%
“…sMa paclitaxel micelles for oral delivery the intestinal epithelium due to tight junction modifications, 5,6 SMA-PTX micelles can pass paracellularly due to the modified tight junctions and reach the tumor site beneath the epithelium. Thus, together these pathways could contribute to the enhanced uptake of SMA-PTX micelles by the colon tumors, resulting in a greater therapeutic effect.…”
mentioning
confidence: 99%